Ionic homeostasis in brain conditioning - Cuomo, Ornella; Vinciguerra, Antonio; Cerullo, Pierpaolo; Anzilotti, Serenella; Brancaccio, Paola; Bilo, Leonilda; Scorziello, Antonella; Molinaro, Pasquale; Di Renzo, Gianfranco; Pignataro, Giuseppe (Frontiers in Neuroscience, 2015)
Most of the research aimed at identifying new stroke therapies focuses on strategies which induce, mimic, or boost endogenous protective responses. Preconditioning is a protective strategy in which a subliminal stimulus is applied before a subsequent harmful stimulus, thus inducing a state of tolerance in which the injury inflicted by the challenge is mitigated. Tolerance may be observed in ischemia, seizure, and infection. Since it requires protein synthesis, it confers delayed and temporary neuroprotection, taking hours to develop, with a pick at 1-3 days. A new promising approach for neuroprotection derives from postconditioning, in which neuroprotection is achieved by a modified reperfusion subsequent to a prolonged ischemic episode. Many pathways have been proposed as plausible mechanisms to explain the neuroprotection offered by preconditioning and postconditioning. Although the mechanisms are not yet fully understood, recent evidence highlights the preminent role of the ionic homeostasis maintenance. The present article will review the role of ionic transporters and channels involved in the control of ionic homeostasis in the neuroprotective effect of ischemic preconditioning and postconditioning in adult brain, with particular regards to Na+/Ca2+ exchangers (NCXs), plasma membrane Ca2+-ATPase (PMCA), Na+/H+ exchanger (NHE), Na+/K+/2Cl− cotransport (NKCC) and acid-sensing ionic channels (ASIC).